1984
DOI: 10.1093/oxfordjournals.jbchem.a134822
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Similarities between “H-450” and Cytochrome P-450

Abstract: The absorption spectrum of reduced H-450 was reversibly affected by a pH change; the Soret peak of the alkaline form was at 448 nm, and that of the acidic form (H-420) at 425 nm. The same spectral change of conversion of reduced H-450 to H-420 was also produced by the action of n-butanol, urea and p-chloromercuribenzoate. These spectral properties of H-450 were similar to those of the conversion of cytochrome P-450 to cytochrome P-420, suggesting the similar heme environments of these two hemoproteins. Reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 0 publications
5
20
0
Order By: Relevance
“…1, below T c the average x 2 declines with temperature due to the decrease of the Weiss field, which causes the maximum of the distribution function to shift to smaller moments. This is in agreement with earlier results 1,5,6,14,15,17 . The width of the distribution function increases with temperature, which counteracts the decrease of the local moment.…”
Section: Thermodynamic Properties: Monte Carlo and Mean-field Resupporting
confidence: 94%
See 1 more Smart Citation
“…1, below T c the average x 2 declines with temperature due to the decrease of the Weiss field, which causes the maximum of the distribution function to shift to smaller moments. This is in agreement with earlier results 1,5,6,14,15,17 . The width of the distribution function increases with temperature, which counteracts the decrease of the local moment.…”
Section: Thermodynamic Properties: Monte Carlo and Mean-field Resupporting
confidence: 94%
“…A large amount of work has been devoted to the thermodynamics of itinerant magnets using phenomenological Ginzburg-Landau models for weak ferromagnets 1,2,3 or the Hubbard model and the functional integral methods. 1,4,5,6 These studies have clarified the role of LSF in thermodynamics and explained the observed behavior of the paramagnetic susceptibility. However, these methods are unsuitable for quantitative studies of realistic materials.…”
Section: Introductionmentioning
confidence: 94%
“…Following deoxygenation [24], the sample was reduced by the addition of 5 μl of a deoxygenated saturated solution of sodium dithionite using a Hamilton gastight syringe. The success of heme iron reduction was monitored spectroscopically [25]. After the reduction was completed, the CBS activity was determined under anaerobic conditions at physiological pH 7.4.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…It is rather astonishing that all the characters which make Ni a model of itinerant ferromagnetism amount finally t o the addition of a T-independent Pauli-like susceptibility xo. Perhaps this has to do with the fact that in Ni the spin length above Tc is only weakly temperature-dependent [20], so that it closely resembles the behavior of localized spin models. Fig.…”
Section: Otdered Ferronragnetsmentioning
confidence: 99%